2004
DOI: 10.1002/maco.200303722
|View full text |Cite
|
Sign up to set email alerts
|

Stress corrosion cracking behaviour of Al‐Li alloy 8090‐T8171 plate exposed to various synthetic environments

Abstract: The stress corrosion cracking (SCC) behaviour of 8090‐T8171 plate material was investigated in short transverse direction performing constant load tests and constant extension rate tests under permanent immersion conditions. At an applied stress of 100 MPa, smooth round tensile specimens were exposed to synthetic environments containing chlorides and various nonhalide anions. Environment‐induced cracking was not observed in aqueous solutions of 0.6 M NaCl, LiCl, NH4Cl, or MgCl2. In 0.6 M NaCl solutions contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Once the amount of Fe was increased more than 10 wt.%, the dissolution of Fe decreased and ultimate tensile strength decreased [23]. Thus, it was suggested from the above literature that more than 10 wt.% Fe cannot be used to obtain a supersaturated solution of Al-Fe alloys for application.Al and their alloys are known to exhibit good corrosion resistance due to the development of an oxide layer on the surface [1,2,[8][9][10][11][12][13][25][26][27][28][29][30]. However, coarse-grained Al exhibits uniform and pitting corrosion when immersed in acidic or harsh atmospheric conditions [12][13][14]27,30].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Once the amount of Fe was increased more than 10 wt.%, the dissolution of Fe decreased and ultimate tensile strength decreased [23]. Thus, it was suggested from the above literature that more than 10 wt.% Fe cannot be used to obtain a supersaturated solution of Al-Fe alloys for application.Al and their alloys are known to exhibit good corrosion resistance due to the development of an oxide layer on the surface [1,2,[8][9][10][11][12][13][25][26][27][28][29][30]. However, coarse-grained Al exhibits uniform and pitting corrosion when immersed in acidic or harsh atmospheric conditions [12][13][14]27,30].…”
mentioning
confidence: 99%
“…This could be due to the presence of less grain-boundary volume in coarse-grained materials than nanocrystalline materials [34,35]. Based on several earlier investigations, it was observed that the corrosion behavior of nanocrystalline materials is dependent on several factors, such as alloying element [25], manufacturing process [36,37], microstructure type [38,39] and environmental conditions [40,41].From the above literature, it was found that there is a lack of information on the effect of Fe addition in an Al matrix using a mechanical-alloying and sintering process in terms of morphological and corrosion characteristics. In the present study, we fabricated Al and Al-Fe alloys with the incorporation of 2 wt.%, 5 wt.%, and 10 wt.% Fe using an MA technique followed by the sintering process.…”
mentioning
confidence: 99%